Iowa RBA, January 6, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for January 6, 1997. Highlights of the update include sightings of a Pinyon Jay, a Varied Thrush, three Long-tailed Ducks, a first-year Black-legged Kittiwake, a first-year Mew Gull, and a first-year Thayer's Gull. Also included is an update to the Iowa RBA with a report of the continued presence of an Evening Grosbeak and a sighting of two Long-eared Owls. Epson - sheet feed/flatbed